2019
DOI: 10.1111/ejss.12793
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of C and N modules in biogeochemical crop and grassland models following manure addition to soil

Abstract: Process‐based crop and grassland models estimating carbon (C) and nitrogen (N) dynamics are widely used to investigate best management practices in agriculture. They integrate several processes in a complex structure, but studies where modules corresponding to specific processes extracted from the whole model structure are assessed independently are uncommon. With the support of documented aerobic incubation trials in manure‐amended soils, a sensitivity analysis was performed on the C–N cycling processes of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A varying number of pools (often including inert and slow‐decomposing organic matter and microbial biomass) linked by first‐order equations is usually simulating both C and N fluxes within and between each pool (Falloon & Smith, 2010). However, different models vary considerably in the underlying assumptions and C processes in current models, for example, regarding number of pools, type of decomposition kinetics used and processes regulating SOC retention (Cavalli et al., 2019; Manzoni & Porporato, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A varying number of pools (often including inert and slow‐decomposing organic matter and microbial biomass) linked by first‐order equations is usually simulating both C and N fluxes within and between each pool (Falloon & Smith, 2010). However, different models vary considerably in the underlying assumptions and C processes in current models, for example, regarding number of pools, type of decomposition kinetics used and processes regulating SOC retention (Cavalli et al., 2019; Manzoni & Porporato, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A varying number of pools (often including inert and slow-decomposing organic matter and microbial biomass) linked by first-order equations is usually simulating both C and N fluxes within and between each pool (Falloon & Smith, 2010). However, different models vary considerably in the underlying assumptions and C processes in current models, for example, regarding number of pools, type of decomposition kinetics used and processes regulating SOC retention (Cavalli et al, 2019;Manzoni & Porporato, 2009). Each model offers a distinctive synthesis of scientific knowledge (Brilli et al, 2017) and multi-model ensembles developed from several models may reduce uncertainties in biological and physical outputs that occur over large scales, such as regions and continents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding C-N fluxes, the two grassland models agreed to some extent across study areas and pasture macro-types, with differences in magnitude and patterns likely associated with the inherent structure of each specific C and N sub-model (e.g. Cavalli et al, 2019). The higher C uptake Ceschia et al, 2010;Zeeman et al, 2010Zeeman et al, , 2019.…”
Section: Analysis Of Climate-change Impacts and Adaptation Strategiesmentioning
confidence: 88%
“…Large variability in the predictions has been shown across models when using the same conditions [140], thus it complicates the selection of a model. Various authors have reviewed the generalities, limitations, accuracy, and sensitivity of different models without a clear answer on how to define that a model would perform better than other [136], [138], [140]- [143]. Multi-model comparison studies have revealed that using an ensemble of models (i.e., 13 [144]; 2-4 with site-specific calibration [139]) may provide more reliable results than single models.…”
Section: Soc Modelingmentioning
confidence: 99%